2018
DOI: 10.1111/lam.13010
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and genome analysis of a lyticPasteurella multocidaBacteriophage PMP-GAD-IND

Abstract: The present work is a part of research for the development of an improved phage lysate marker vaccine and a companion DIVA assay against haemorhagic septicaemia. This study describes the isolation and genome analysis of PMP-GAD-IND a lytic Pasteurella multocida bacteriophage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Electron microscopy showed that the appearance of PHB01 was composed of an isometric polyhedral head approximately 55 nm in diameter and a short tail ~13 nm in length (Figure 2B). These morphological characteristics are quite similar to phage PHB02, a lytic P. multocida phage belonging to the family Podoviridae in the order Caudovirales [17], but differ from the reported Pasteurella phages in family Siphoviridae , which have long noncontractile tails (≥100 nm) [18,39,40] and/or in the family Siphoviridae with long, contractile tails (≥100 nm) [19]. These findings suggest that PHB01 is a member of the family Podoviridae in the order Caudovirales.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Electron microscopy showed that the appearance of PHB01 was composed of an isometric polyhedral head approximately 55 nm in diameter and a short tail ~13 nm in length (Figure 2B). These morphological characteristics are quite similar to phage PHB02, a lytic P. multocida phage belonging to the family Podoviridae in the order Caudovirales [17], but differ from the reported Pasteurella phages in family Siphoviridae , which have long noncontractile tails (≥100 nm) [18,39,40] and/or in the family Siphoviridae with long, contractile tails (≥100 nm) [19]. These findings suggest that PHB01 is a member of the family Podoviridae in the order Caudovirales.…”
Section: Discussionmentioning
confidence: 85%
“…Since then, there have been no reports on P. multocida phages for 12 years. In 2018, the first complete genome sequences of lytic bacteriophages for P. multocida capsular types A and B were reported [17,18]. However, there is still a lack of reporting on lytic bacteriophages for P. multocida strains of other capsular types (D, E, and F).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations